2004
DOI: 10.5194/angeo-22-3009-2004
|View full text |Cite
|
Sign up to set email alerts
|

Cluster survey of the high-altitude cusp properties: a three-year statistical study

Abstract: Abstract. The global characteristics of the high-altitude cusp and its surrounding regions are investigated using a threeyear statistical survey based on data obtained by the Cluster spacecraft. The analysis involves an elaborate orbit-sampling methodology that uses a model field and takes into account the actual solar wind conditions and level of geomagnetic activity. The spatial distribution of the magnetic field and various plasma parameters in the vicinity of the low magnetic field exterior cusp are determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
91
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 34 publications
7
91
0
Order By: Relevance
“…Lately, some studies have been done on the open-closed field line boundary and the cusp and the dependence on the IMF (Pitout et al, 2006;Hu et al, 2007;Cai et al, 2009), where it was found that the reconnection line moves equatorward/poleward of the cusp when the IMF changes sign, and compatible with the pictures obtained from statistical studies (Lavraud et al, 2004(Lavraud et al, , 2005. The cusp was observed to react rather fast to local (i.e.…”
Section: Introductionsupporting
confidence: 58%
“…Lately, some studies have been done on the open-closed field line boundary and the cusp and the dependence on the IMF (Pitout et al, 2006;Hu et al, 2007;Cai et al, 2009), where it was found that the reconnection line moves equatorward/poleward of the cusp when the IMF changes sign, and compatible with the pictures obtained from statistical studies (Lavraud et al, 2004(Lavraud et al, , 2005. The cusp was observed to react rather fast to local (i.e.…”
Section: Introductionsupporting
confidence: 58%
“…This suggests an alternative path of entering the low-altitude polar region. Some authors considered that solar wind or magnetosheath electrons could be the main source for downward electrons in the cusp region (Lavraud et al, 2004;Shi et al, 2014;Smith & Lockwood, 1996), and the magnetotail electrons should be the main source for the downward electrons or precipitation in the nightside auroral oval (Barth et al, 2004;Berko & Hoffman, 1974;Crooker, 1992;Teste et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The exterior cusp has been shown to have three boundaries (Lavraud et al, 2004a;Paschmann et al, 1976;Haerendel et al, 1978;Onsager et al, 2001): the day-side plasma sheet on the sunward side, the tail-lobe or mantle on the night-side, and the magnetosheath in the exterior. Though it has been suggested that the outer boundary may represent an intermediate or slow transition (Lavraud et al, 2002) Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%